Understanding determinants of outward foreign direct investment: the role of economic policy uncertainty, institutional quality, and globalization - Ölmez, Fevzi; Bilgiç, Emre; Aydın, Esra (Universidad ESAN. ESAN Ediciones, 2024)
Purpose: This research aims to investigate the role of the economic policy uncertainty (EPU) in the outward FDI (OFDI) of the United Kingdom (UK) by considering the institutional quality (IQ) and globalization level of the host country as contextual factors. Design/methodology/approach: The UK’s OFDI to its twenty partners is analyzed by using the factor augmented model for the 2005–2019 period. Findings: The results show that the EPU of the host country has a negative and significant effect on the UK's OFDI. Furthermore, the findings surprisingly illustrate that the globalization level of the host country has a negative and significant impact on the UK's OFDI. In terms of IQ, this study indicates that, while government effectiveness and regulatory quality have a negative and significant influence on the UK's OFDI, the rule of law has a positive and significant effect on the UK's OFDI. Originality/value: This will be one of a few studies considering OFDI in the scope of EPU. Also, the contradicting results of the study add unique perspectives to the literature about the relationship between OFDI, globalization, and IQ.
Keywords: Outward FDI; EPU; IED saliente; Institutional quality; EPU; Globalization; Calidad institucional; Globalización; Factor augmented model; Modelo factorial aumentado; https://purl.org/pe-repo/ocde/ford#5.02.04